2018
DOI: 10.18542/rebac.v14i1.7155
|View full text |Cite
|
Sign up to set email alerts
|

Controle Inadvertido Pela Localização Em Tarefas De Matching-to-Sample Com Indivíduos Com Transtorno Do Espectro Autista

Abstract: Estudos com sujeitos não humanos mostraram que o estabelecimento de controle inadvertido pela localização pode prejudicar a aquisição de relações condicionais em procedimentos de matching-to-sample (MTS). O objetivo do Experimento 1 foi verificar se esse fenômeno ocorreria com indivíduos com Transtorno do Espectro Autista (TEA) em sessões de treino com MTS sem procedimentos adicionais que pudessem favorecer a aquisição, tais como procedimentos de esvanecimento, dicas e correção. Todos os três participantes mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
3
0
4
Order By: Relevance
“…Responses were sometimes emitted in all of the trials or none of the trials, while at other times they appeared to be under the control of one compound stimulus or one of the elements of the compound stimulus. These patterns of restricted stimulus control can also be observed when standard MTS procedures are implemented, especially with populations with delayed development, such as Down syndrome and ASD (e.g., Da Hora et al, 2018;Domeniconi et al, 2009;Stromer et al, 1993). However, in the present study, faulty stimulus control that was observed in the pretests was eliminated in the posttests without requiring any supplementary procedures that are often implemented in MTS procedures, such as exclusion (e.g., de Rose et al, 1989Rose et al, , 1996de Souza et al, 2009;Melchiori et al, 2000) or correction procedures in which the same sample and comparison stimuli are repeatedly presented until the participant emits the correct response (e.g., Kangas & Branch, 2008;Sidman, 1971;Sidman & Cresson, 1973;Sidman et al, 1974).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Responses were sometimes emitted in all of the trials or none of the trials, while at other times they appeared to be under the control of one compound stimulus or one of the elements of the compound stimulus. These patterns of restricted stimulus control can also be observed when standard MTS procedures are implemented, especially with populations with delayed development, such as Down syndrome and ASD (e.g., Da Hora et al, 2018;Domeniconi et al, 2009;Stromer et al, 1993). However, in the present study, faulty stimulus control that was observed in the pretests was eliminated in the posttests without requiring any supplementary procedures that are often implemented in MTS procedures, such as exclusion (e.g., de Rose et al, 1989Rose et al, , 1996de Souza et al, 2009;Melchiori et al, 2000) or correction procedures in which the same sample and comparison stimuli are repeatedly presented until the participant emits the correct response (e.g., Kangas & Branch, 2008;Sidman, 1971;Sidman & Cresson, 1973;Sidman et al, 1974).…”
Section: Discussionmentioning
confidence: 94%
“…The Go/No-Go procedure with compound stimuli may benefit populations who present with difficulties in establishing emergent repertoires with MTS, such as children with autism who are at risk of developing restricted stimulus control (e.g., Stromer et al, 1993). For example, the establishment of conditional discriminations using MTS procedures may be difficult for some individuals with autism because they show location bias (e.g., Bourret et al, 2012;Da Hora et al, 2018). When this occurs, the Go/No-Go procedure with compound stimuli can be a good alternative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesse estudo, duas crianças com autismo passaram pelo treino com reforçamento das relações de linha de base (AB/BC) em que deveriam responder (i.e., pressionar a tecla barra de espaço no teclado) diante dos compostos relacionados (R) apresentados na tela e não responder (i.e., não pressionar a tecla) diante de compostos não relacionados (NR). Uma vez que os participantes respondiam em uma única tecla, não havia a possibilidade do desenvolvimento de controle da resposta pela localização dos estímulos que pode ocorrer no MTS com crianças com autismo (e.g., da Hora et al, 2018). Após o estabelecimento das relações AB/BC nos treinos com reforçamento, os participantes realizaram sessões de treino sem consequência e seguiram para os testes de relações emergentes de simetria (BA/CB), transitividade e equivalência (AC/CA) em que responder ou não diante dos compostos R ou NR não era seguido de consequências programadas.…”
unclassified
“…Na ausência desses pré-requisitos, o participante irá apresentar dificuldades no MTS (e.g., Green, 2001). Outro possível problema é que o MTS pode produzir um controle inadvertido do responder pela localização na qual os estímulos são apresentados, independentemente da relação condicional a ser estabelecida com crianças com autismo (e.g., da Hora, Debert, Lafrance, & Miguel, 2018)e outras populações (e.g., Galloway, 1967;Iversen, Sidman, & Carrigan, 1986;Kangas & Branch, 2008), Um procedimento alternativo ao MTS que evitaosproblemassupracitados e estabelece classes de equivalência é o procedimentoGo/no-gocom estímuloscompostos(e.g., (Debert, Amelia Matos, & McIlvane, 2007). Neste procedimento, as respostas são emitidas em um único local (e.g., barra de espaço ou clicar em um botão) e impossibilitam o desenvolvimento de controle pela localização.…”
Section: Sumáriounclassified